2003
DOI: 10.1385/abab:107:1-3:505
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Aspects of Acid Hydrolysis of α-Cellulose

Abstract: Hydrolysis of alpha-cellulose by H2SO4 is a heterogeneous reaction. As such the reaction is influenced by physical factors. The hydrolysis reaction is therefore controlled not only by the reaction conditions (acid concentration and temperature) but also by the physical state of the cellulose. As evidence of this, the reaction rates measured at the high-temperature region (above 200 C) exhibited a sudden change in apparent activation energy at a certain temperature, deviating from Arrhenius law. Furthermore, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(120 citation statements)
references
References 10 publications
4
104
2
10
Order By: Relevance
“…3,5,7 Different catalysts have been used for this reaction, such as metal chlorides, 4,6 acids, or enzymes. 1,31,32 The most common and widely used enzyme for this saccharification of cellulose is cellulase.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,7 Different catalysts have been used for this reaction, such as metal chlorides, 4,6 acids, or enzymes. 1,31,32 The most common and widely used enzyme for this saccharification of cellulose is cellulase.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrated acid plays a dual role in biomass hydrolysis. By disrupting its network of intra-and interchain hydrogen bonds, strong acids decrystallize cellulose and make it accessible to reagents (19); and by catalyzing the hydrolysis of glycosidic bonds, strong acids cleave cellulose and hemicellulose into sugars ( Fig. 1) (4).…”
mentioning
confidence: 99%
“…Xiang et al have reported such a change in the physical structure of a-cellulose from a fibrous form to a gelatinous form when treated with 65% H 2 SO 4 . The change in the physical form of the a-cellulose was attributed to the disruption of the hydrogen bonding network [23]. Lan et al succeeded in transforming crystalline cellulose isolated from sugar cane bagasse to an amorphous form with the aid of ultrasonic irradiation of 2 wt.…”
Section: Resultsmentioning
confidence: 99%